POLITENESS AND SPEECH ACT STRATEGIES IN INTERCULTURAL COMMUNICATION: BASED ON ENGLISH AND UZBEK LANGUAGE MATERIALS - Аmanullayeva Kamola Muminovna; Ergasheva Muxlisa Baxodir kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article comparatively examines politeness strategies and the pragmatic characteristics of speech acts in intercultural communication using English and Uzbek language materials. Drawing on Brown and Levinson’s face theory, Searle’s classification of speech acts, and Leech’s politeness principles, the article analyzes strategies for expressing requests, apologies, offers, and refusals in both languages. The study demonstrates how socio-cultural norms in Uzbek communication, such as shame (uyat), honour (nomus), respect (hurmat), and deference to elders, shape the choice of politeness strategies. Issues of bilingual communication and pragmatic transfer are also addressed.